Cervical Cancer Screening and HPV Vaccine Intentions: An Egyptian Population Assessment through University Channels - Ebeid, Rita Hany (AUC Knowledge Fountain, 2025)
Background: Cervical cancer remains a significant global health burden, disproportionately affecting low- and middle-income countries. While HPV vaccination and cervical cancer screening programs have shown promise in reducing incidence and mortality, access to these interventions remains limited in Egypt. The purpose of this study was to analyze female and male beliefs, knowledge of, and perceptions related to cervical cancer screening and HPV vaccination, and how these factors influence women and men’s intentions to respectively undergo or promote these behaviors in Egypt. This study also aimed to develop recommendations for more effective cervical cancer prevention measures that promote greater uptake among women, and greater prevention promotion among men. Methods: Based on a quantitative cross-sectional study design, a self-administered questionnaire was developed according to the Theory of Reasoned Action and Health Promotion Model, and measured individual intention to engage in or promote cervical cancer screening and HPV vaccination among the target population. Non-random convenience sampling among the Egyptian population through university channels was utilized. Correlation analysis was performed to assess the associations between the measured variables. Multi-regression analysis was also conducted to predict female and male intention separately. Results: With a total of 281 survey respondents, the research results revealed that for females, greater perceived benefits, fewer perceived barriers, higher self-efficacy, positive activity-related affect, a supportive subjective norm, and favorable situational influences were positively correlated with screening and vaccination intention. For males, the factors influencing promotion intention were perceived self-efficacy and activity-related affect. Activity-related affect and situational influences were found to be statistically significant predictors of females’ intention, and vaccination status and activity-related affect as statistically significant predictors of males’ intention. Conclusion: This study is among the first to comprehensively investigate factors influencing cervical cancer screening and HPV vaccination intentions among Egyptians reached through university channels. The findings emphasize the need for government-supported, gender-specific interventions that increase positive activity-related affect for both genders, improve situational influences for women, and emphasize men's role in health promotion to increase engagement in these preventive health behaviors, ultimately improving cervical cancer prevention outcomes in Egypt.